2007
DOI: 10.2353/ajpath.2007.070132
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Gene Survivin Is Highly Expressed in Adult Renal Tubular Cells

Abstract: The inhibitor of apoptosis protein survivin is of critical importance for regulation of cellular division and survival. Published data point to a restricted function of survivin in embryonic development and cancer; thus survivin has been broadly proposed as an ideal molecular target for specific anti-cancer therapy. In contrast to this paradigm, we report here broad expression of survivin in adult differentiated tissues, as demonstrated at the mRNA and protein levels. Focusing on the kidney, survivin is strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
4
46
1
1
Order By: Relevance
“…The finding of survivin expression in epithelia of the placenta, gastrointestinal tract and skin are in agreement with multiple immunohistochemical studies of adult human and 29 rodent tissues (Chiodino et al, 1999;Gianani et al, 2001;Ding et al, 2006;Lechler et al, 2007;Piras et al, 2007) and with expression data available from a publicly accessible repository (http://www.proteinatlas.org/). Positive expression in several further organs including testis, kidney, liver and brain ( Kobayashi et al, 1999;Altura et al, 2003;Moon and Tarnawski, 2003;Lechler et al, 2007) is supported by at least one previous study with human tissues and by data from the protein atlas.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The finding of survivin expression in epithelia of the placenta, gastrointestinal tract and skin are in agreement with multiple immunohistochemical studies of adult human and 29 rodent tissues (Chiodino et al, 1999;Gianani et al, 2001;Ding et al, 2006;Lechler et al, 2007;Piras et al, 2007) and with expression data available from a publicly accessible repository (http://www.proteinatlas.org/). Positive expression in several further organs including testis, kidney, liver and brain ( Kobayashi et al, 1999;Altura et al, 2003;Moon and Tarnawski, 2003;Lechler et al, 2007) is supported by at least one previous study with human tissues and by data from the protein atlas.…”
Section: Discussionsupporting
confidence: 87%
“…Positive expression in several further organs including testis, kidney, liver and brain ( Kobayashi et al, 1999;Altura et al, 2003;Moon and Tarnawski, 2003;Lechler et al, 2007) is supported by at least one previous study with human tissues and by data from the protein atlas. One study in particular has demonstrated, with different methods, high survivin levels in the adult renal proximal tubules (Lechler et al, 2007 (Fukuda and Pelus, 2006) were not included in the present study but these tissues from dogs might also express survivin. In the present study, a more extensive identification of cell types was not possible in the tissue microarrays due to the limited amount of tissue examined and the limited number of tissues included.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…36 Survivin, another IAP, has recently been identified as a constitutive prosurvival molecule in tubular cells that protects from experimental AKI. 37,38 …”
Section: Overview Of Apoptosis Pathwaysmentioning
confidence: 99%